Structural, Optical, and Dielectric Studies on Transition Metals Doping (Cu, Ni) in MgFe2o4 Ferrites - Dhahri, Siwar; Omri, Aref; Dhaou, Mohamed Houcine; Dhahri, Essebti; Graça, Manuel P.F.; Brito, Anna B.; FAUSTO, RUI; Pina, João; Costa, Benilde F.O. (Elsevier Ltd., 2025)
Spinel ferrites are increasingly researched for their tunable optical and electrical properties, with applications in electronic devices and microwave absorption. This study investigates Mg0.5Cu0.3Ni0.2Fe2O4 synthesized via sol-gel auto-combustion, yielding a single-phase cubic spinel structure (Fd-3m) with crystallite sizes of ∼1.1 μm. XRD and Raman spectroscopy confirmed the phase purity and identified five active modes (A1g, Eg, 3T2g). Optical analysis revealed a direct bandgap (Eg = 2.335 eV), low Urbach energy (Eu = 0.2386 eV), and strong UV–Vis absorption, indicating high crystallinity and suitability for optoelectronics. Electrical measurements demonstrated semiconducting behavior with an activation energy (Ea) of 0.34 eV, governed by the Correlated Barrier Hopping (CBH) model. Dielectric studies showed high permittivity (ε' > 103 at low frequencies) and significantly reduced loss (tan δ < 0.1 at 106 Hz), confirming efficacy in high-frequency energy transmission/storage. The synergistic Cu/Ni doping enables tailored structural, optical, and dielectric properties, positioning this material as a promising candidate for high-frequency electronics, energy storage systems, and solar cells.
Keywords: CBH Model; Dielectric Constant; Energy Storage; Optical Bandgap; Sol-gel Synthesis; Spinels; Urbach Energy